Validity of Problem-Based Learning (PBL) Module of Automation for Personnel Governance - Nisa', Khoirun; Rosy, Brillian (Journal of Office Administration : Education and Practice, 2024)
In the learning process at a Vocational High School, a teacher requires learning materials that are by the 2013 Curriculum to facilitate students in increasing their learning independence. This research aims to explain the validity of the product resulting from the development of a problem-based learning (PBL) employee management automation module based on student needs. This research method is a type of development research (R&D) using the ADDIE development model. The research focused on the module assessment results of validation experts consisting of material, language, and graphics experts. The research results show that the module is included in the very appropriate criteria by experts with an average score of 96% from a maximum score of 100%. The results of the material expert assessment were 90%, the language expert assessment was 100%, and the graphics expert assessment was 97%. This states that the module developed by researchers is suitable for use in the learning process according to learning objectives and student competency standards.